2012
DOI: 10.1115/1.4006141
|View full text |Cite
|
Sign up to set email alerts
|

Array of Thermoelectric Coolers for On-Chip Thermal Management

Abstract: Site-specific on-demand cooling of hot spots in microprocessors can reduce peak temperature and achieve a more uniform thermal profile on chip, thereby improve chip performance and increase the processor’s life time. An array of thermoelectric coolers (TECs) integrated inside an electronic package has the potential to provide such efficient cooling of hot spots on chip. This paper analyzes the potential of using multiple TECs for hot spot cooling to obtain favorable thermal profile on chip in an energy efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 25 publications
(45 reference statements)
0
10
0
Order By: Relevance
“…[26] and t 1/2 in Ref. [31]. Thus, the divergence could be attributed to the differences of the boundary conditions and the pulse amplitude and width.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…[26] and t 1/2 in Ref. [31]. Thus, the divergence could be attributed to the differences of the boundary conditions and the pulse amplitude and width.…”
Section: Introductionmentioning
confidence: 92%
“…In addition, they also concluded that the monotonically increasing pulse shape was more appropriate to achieve the maximum supercooling capacity along with the maximum holding duration and the fastest recovery time to the next new steady state. Sullivan et al [31] analyzed and compared four different pulse shapes (t 0 , t 1/2 , t 1 , and t 2 ). They presented that the best cooling at the hot spot was obtained by using square root pulse with a maximum temperature drop of 10.4 C, however, the linear and parabolic pulses cooled the hot spot by 9.7 C and 8.1 C, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sullivan et al [3] used the thin-film thermoelectric cooler (thin film TEC) to carry out the heat dissipation for the chip set of microprocessor through 3x3 matrix arrangement. It was found when 9 Thin film TEC were activated simultaneously, the maximum temperature reduction of the chip would be 11 within 0.03 seconds, but the temperature rise rapidly thereafter.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work [22,23], we have developed numerical model of a package with embedded TECs. The dimensions and properties of these devices are similar to the devices fabricated by Chowdhury et al [11].…”
Section: Introductionmentioning
confidence: 99%